Air Transport and Local Development in Belgium and The Netherlands - Hugo Gordijn (European Regional Science Association (ERSA), 2013)
The impact of an airport on spatial economic development is cited to justify investments. Local governments are of the opinion that an airport can have a positive effect on a region. However, there are disagreements about just how much extra employment and added value an airport generates. It differs between 200 en 2000 extra jobs per million passengers. The paper examines the causes of these large discrepancies. Questions of definitions and the degree to which indirect employment, induced effects and catalytic effects are taken into account muddle the comparability. The demarcation of the terrain of an airport is also different; sometimes it?s broad, sometimes limited. Another limitation is the fact that all Ryanair employees have an Irish employment contract, and therefor don?t show up in the statistics at Charleroi. The aforementioned reasons indicate why a straight comparison between different airports is not possible This paper contains recent data about the airport development of Dutch and Belgian airports. It shows significant differences between the airports. Small airports have a relatively large amount of employees compared to their production. Large airports benefit from their greater scale. Timeseries for employment and added value show an increase in labor productivity. The total number of jobs on Belgian airports has decreased owing to the demise of SABENA in 2001. The paper also shows how the stimulating development policy of the Walloon government leads to a sharp increase in employment on the two Walloon airports : Charleroi as an airport for low-cost airlines and Liège-Bierset as an airport for express-freight. Employment has continuously grown at Amsterdam Schiphol airport since the 1970?s. In the early years this was mainly through the growth of passenger numbers and the development of the hub-function. In more recent years the growth has been spurred by the demand for increased safety measures, but the most significant contribution to the recent growth of employment at Schiphol has been the development of the Airport-city. The presence of a home-base carrier has shown to have the largest effect on employment. JEL-code : Transportation Systems R40 - General
Keywords: R40; 330; Transportation Systems